The risk mapping for hospitals and the impact for the transport in the Zlín Region - Vichova, Katerina; Hromada, Martin (Journal of emergency management, 2020)
The authors have witnessed an increase in crisis, resulting in significant loss of life and impact on the economy of a given country in recent years. In spite of the efforts and measures of each country's government to reduce the impact of the crisis, this trend has not been avoided. This trend is observed at all levels-in municipalities, in the Czech Republic, but also the world. Extraordinary events or a crisis ordinarily have the so-called cascade effect that causes other extraordinary events. An example of this may be windstorm, resulting in a power outage. Significant power supply outages are observed in hospitals. Here, it is essential for acute care clients to have a regular intake of electrical energy to ensure their life functions. The introduction of this article refers to the authors, which describes the situation with the increasing number of emergencies. Second, there are described possible cascade effect of the crises. The third part of this article is focused on the flood risk affecting hospitals. The aim of this article is to carry out risk mapping for selected hospitals in the Czech Republic, specifically in the Zlín Region.
Keywords: záplavy; Hospitals; Česká republika; Humans; Wind; plánování postupu v případě katastrof; lidé; hodnocení rizik; vítr; Electric Power Supplies; Floods; nemocnice; Disaster Planning; Czech Republic; Emergencies; Risk Assessment; náhlé příhody; zdroje elektrické energie